After Heidegger: Transubstantiation - Hemming, Laurence Paul (Heythrop journal, 2000)
Recent debate over transubstantiation (especially Jean-Luc Marion's defence of it) has concentrated either on transubstantiation as a kind of embarrassment in consequence of modern physics, or on the extent to which it is both a doctrine elaborated in the light of metaphysics and recoverable in consequence of metaphysics having been overcome. In this sense the tension between Aquinas' apparently metaphysical formulation of the doctrine and the less overtly metaphysical formula adopted by the Council of Trent (in its refusal to speak of ‘accidents’) has indicated a way of ‘rescuing’ or ‘recovering’ the doctrine. This article argues that such a recovery is a false trail. Pope Paul VI was right to be wary of relativising the Eucharistic event to the believing community in any doctrine of transignification. Alternatively, attempts like Chauvet's and Macquarrie's to restate Eucharistic event in terms of Heidegger's Geviert presuppose Heidegger has succeeded in destroying the metaphysics of presence, so that they can use the fruits of his researches. What is actually at issue in thinking through transubstantiation is how the doctrine relates to conceptions of the physical: Aristotelian, what comes to be Newtonian, or postmodern conceptions which appear to eschew physics altogether. Heidegger's contribution to the debate would better point to how knowing anything means being included in and (self-) disclosed by what I know. A re-investigation of transubstantiation might therefore take into account the extraordinary reappearance of the term ‘transubstantiation’ in current non-theological investigations of performativity (especially in the work of Judith Butler). Here transubstantiation would include not the maximal meaning of bread and wine as signs constituted in das Geviert, ‘after’ substance has been critiqued, but their minimality, in enacting a change in (our) substance (self-realising). This would confirm the divinising meaning of the Eucharistic event, which stresses how we are caught up into the divine. Thus, whereas in transignification the Eucharistic event occurs in consequence of the will of the community of believers, in transubstantiation it is the enactment of the community as community that is at issue, an enactment in consequence of no act of will of its own. In terms of the postmodern and non-theological appropriation of the word transubstantiation, this means that I who participate in the Eucharistic am re-ordered, or re-materialised, or ‘trans-substantiated’ in the Eucharistic event.